Analisis Kebijakan Merdeka Belajar - Aliyah, Andi Dzakiyatul; Dina, Eka Salma; Saifuddin, Muhammad Amril (YASIN, 2023)
Quality education is education that is able to carry out the process of maturing the quality of students which is developed by freeing students from ignorance and incompetence. With quality education, generations or superior human resources will be born in all aspects of life. Many policies have been carried out by the government to improve the quality of education, such as the independent learning policy. Educational institutions are no less lagging behind in improving the quality of education by continuing to improve the quality of human resources, as well as the quality of learning. The method used in this research is a qualitative descriptive method using the literature study method. The literature used is literature that is relevant to the problems and research objectives, such as books, journal articles, proceedings and research research reports that aim to describe the independent learning policy as an effort to improve the quality of education. While the sources taken are from scientific books that have been published with the intention of being used as reference material. The results of this study indicate that the implementation of the independent learning policy can be carried out through improving the quality of education, the learning process, commitment from teachers, support from school principals, and the educational curriculum.